2010
DOI: 10.2119/molmed.2009.00105
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Insulin Sensitivity and Caveolin-1 Expression by Orchidectomy in a Nonobese Type 2 Diabetes Animal Model

Abstract: Previously, we found that male JYD mice developed type 2 diabetes but female mice did not, and that decreased expression levels of caveolin-1 were correlated with the development of a diabetic phenotype in these mice. Therefore, we hypothesized that sex hormones affect the expression of caveolin-1 and contribute to the development of insulin resistance and hyperglycemia in JYD mice. We used glucose and insulin tolerance tests to examine insulin sensitivity in male, female and orchidectomized male JYD mice. Glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 42 publications
(48 reference statements)
1
16
0
Order By: Relevance
“…Notably, Cav1-deficient mice have a lean phenotype (Razani et al 2002). Furthermore, CAV1 expression is dependent on androgens and exercise (Baehr et al 2011, Oh et al 2011. These data from Cav-deficient mice indicate that Cav1 may play a key role in glucocorticoid regulation of the insulin pathway, thereby contributing to muscle atrophy.…”
Section: Introductionmentioning
confidence: 94%
“…Notably, Cav1-deficient mice have a lean phenotype (Razani et al 2002). Furthermore, CAV1 expression is dependent on androgens and exercise (Baehr et al 2011, Oh et al 2011. These data from Cav-deficient mice indicate that Cav1 may play a key role in glucocorticoid regulation of the insulin pathway, thereby contributing to muscle atrophy.…”
Section: Introductionmentioning
confidence: 94%
“…A variety of studies have raised the possibility that estrogens have more prominent effects than testosterone in diabetes and cancer [35]. Moreover, conflicting results have been obtained regarding the role of testosterone in diabetes [19], [36], [37].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that CAV1 is an important target protein in E2- as well as DHT-dependent regulation of various metabolic pathways, particularly in cancer and diabetes [33], [35], [41], [42].…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of previous work in relevant animal models (and humans) indicate that estrogens protect pancreatic islet cells from loss of function and degeneration [43]. With particular reference to this cross, in B6D2F1 hybrid mice-the F1 offspring of B6 dams crossed with D2 sires-males spontaneously develop adult onset, non-obese type II diabetes [44,45]. Thus, there is a rich literature indicating strong genetic effects on glucose metabolism in the B6 and D2 genetic background, and a male-specific form of diabetes is known to spontaneously occur in hybrids of this strain.…”
Section: Association Of Pathological Mediators With the Chr 13 Qtlmentioning
confidence: 99%